2016
DOI: 10.1097/sla.0000000000001249
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Prospective Comparative Study of Robotic Versus Laparoscopic Gastrectomy for Gastric Adenocarcinoma

Abstract: The use of robotic systems is assumed to provide a technically superior operative environment for minimally invasive surgery. However, our analysis of perioperative surgical outcomes indicated that robotic gastrectomy is not superior to laparoscopic gastrectomy. Clinical trials identification: NCT01309256.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
199
5
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 254 publications
(221 citation statements)
references
References 37 publications
6
199
5
5
Order By: Relevance
“…A recent multicenter prospective comparative study showed similar overall complication rates of 11.9% in the robotic group and 10.3% in the laparoscopic group and the rate of major complications of 1.1% in both groups 29. So far, one publication has shown significantly fewer complications for robotic gastrectomy in comparison to laparoscopic gastrectomy regarding postoperative pancreatic fistula at a rate of 2.3% vs 11.4%, respectively.…”
Section: Perioperative Outcomesmentioning
confidence: 93%
See 3 more Smart Citations
“…A recent multicenter prospective comparative study showed similar overall complication rates of 11.9% in the robotic group and 10.3% in the laparoscopic group and the rate of major complications of 1.1% in both groups 29. So far, one publication has shown significantly fewer complications for robotic gastrectomy in comparison to laparoscopic gastrectomy regarding postoperative pancreatic fistula at a rate of 2.3% vs 11.4%, respectively.…”
Section: Perioperative Outcomesmentioning
confidence: 93%
“…A recent multicenter prospective comparative study also showed no difference in hospital stay between robotic and laparoscopic gastrectomy 29. However, a retrospective study demonstrated a reduction in hospital stay between the two approaches with a mean of 14 days in the robotic group and 15 days in the laparoscopic group 28.…”
Section: Perioperative Outcomesmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, a prospective, multicenter comparative study was conducted in Korea and the short-term outcome was reported recently (NCT01309256). There were no significant differences in morbidity and mortality rates, estimated blood loss, rates of open conversion, diet build-up, and length of hospital stay, but significantly higher cost and longer operation time in robot group were observed as expected (42). Studies on the long-term surgical outcomes are on progress.…”
Section: Robotic Surgery For Gastric Cancermentioning
confidence: 99%